FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP RENDAHNYA MINAT DALAM MENGGUNAKAN KONTRASEPSI MOW PADA PUS DI DESA TANON KECAMATAN PAPAR KABUPATEN KEDIRI - Ika Kristina Dewi Agustin; Retno Palupi Yonni Siwi; Sugiyanto Sugiyanto (STRADA : Jurnal Ilmiah Kesehatan, 2013)
Its low enthusiasm use the contraception MOW can be influenced various factor, good motivate the, knowledge and also husband support. This research target to know the factor having an effect on to lowering enthusiasm in using contraception MOW at PUS in Countryside of Tanon Subdistrict Papar Regency Kediri. Used design by analytic of correlation with the approach of cross sectional. Population is all PUS in Countryside of Tanon Subdistrict Papar Regency Kediri by sampel 41 responder taken with the technique of purposive sampling. Free variable is factor influencing enthusiasm use the MOW like motivation, knowledge, husband support and trussing of enthusiasm use the contraception MOW collected by kuesioner. Data expressed in nominal scale and ordinal and analysed with the Doubled test Regression Logistics. From research result got by most responder own the high motivation that is 28 responder ( 68,3%), mostly own the good knowledge about MOW that is 121 responder ( 51,9%), mostly there is husband support to use the MOW that is 25 responder ( 61%), mostly hanker to MOW that is 21 responder ( 51,2%) and there is influence which signifikan of motivation, knowledge and husband support with the enthusiasm WUS in use of contraception MOW ( p = 0,003 < 0,05 hence Ho refused). This matter is caused to incidence of enthusiasm use the MOW needed by knowledge of concerning MOW, so that arise the strong motivation to use it, but still need the its husband support. Is concluded that factor motivate the, knowledge and husband support still be needed to to generate the enthusiasm use the contraception MOW. Suggested that by a countryside midwife cooperate with the worker KB from subdistrict for the socialization of contraception of MOW and routine safari KB so that coverage MOW mount.